Maternal age and child development outcomes at age five in Australian Aboriginal and non-Aboriginal children: a population data linkage study: IJPDS (2017) Issue 1, Vol 1:090, Proceedings of the IPDLN Conference (August 2016) - Falster, Kathleen; Hanly, Mark; Banks, Emily; Lynch, John; Jorgensen, Mikaela; Brownell, Marni; Jorm, Louisa (International Journal of Population Data Science, 2017)
ABSTRACT Objectives Almost one-fifth of Australian Aboriginal mothers give birth before 20 years of age compared with 3% of non-Aboriginal mothers. We aim to quantify the effect of maternal age at birth on child development outcomes in Aboriginal compared with non-Aboriginal children. Approach The ‘Seeding Success’ study cohort comprises an almost complete population of children who started school in Australia’s most populous state, New South Wales (NSW), in 2009 or 2012, and were born in NSW, identified by linking Australian Early Development Census (AEDC) data to perinatal and birth registration datasets. Of the 154,936 children in the cohort, 8001 (5%) were Aboriginal. We calculated the risk of developmental vulnerability on one or more AEDC domains by maternal age at birth and Aboriginality. Risk differences and risk ratios (RR) were estimated as measures of absolute and relative inequalities, respectively. Multilevel Poisson regression was used to test the effect of maternal age on child development by Aboriginality. Results 1383 (17%) Aboriginal children were born to a mother <20 years compared with 4310 (3%) non-Aboriginal children. Among Aboriginal and non-Aboriginal children, the risk of developmental vulnerability decreased with increasing maternal age up to 35 years; the risk increased for children born to mothers >35 years. Among Aboriginal children, the risk decreased from 46% (95%CI, 39-52) to 31% (95%CI, 24-38) in children born to mothers’ aged ≤16 years to age 35 years, respectively. In non-Aboriginal children, the risk decreased from 38% (95%CI, 33-43) to 16% (95%CI, 15-17) in those born to mothers’ aged ≤16 years to 35 years, respectively. Risk differences and risk ratios for developmental vulnerability between Aboriginal and non-Aboriginal children increased with increasing maternal age. Compared to non-Aboriginal children born to mothers aged ≥20 years (ref group, RR, 1.0), the RR for developmental vulnerability was 1.7 (95% CI, 1.6-1.9) for non-Aboriginal children born to mothers aged <20 years; 1.6 (95% CI, 1.6-1.7) for Aboriginal children born to mothers aged ≥20 years; and 2.2 (95% CI, 2.0-2.3) for Aboriginal children born to mothers aged <20 years. Conclusion Children born to very young mothers had a high risk of vulnerability regardless of Aboriginality, whereas Aboriginal children had a greater risk of developmental vulnerability across the rest of the maternal age range. Both absolute and relative inequalities in developmental vulnerability increased with increasing maternal age. Early intervention and support services targeted at Aboriginal mothers and their children, regardless of the mother’s age, may reduce this inequality.